HELP-SEEKING DIFFICULTY AND BURDEN IN DEMENTIA CAREGIVERS UPON REACHING AN EARLY DETECTION SERVICE. (11th November 2018) - Ng, C; Cai, X; Wong, G
Abstract: Background: Barriers affecting people with suspected dementia to seek help have been identified. The experience of people who sought help from specialised early detection service for dementia is still unknown. This study explores perceived help-seeking difficulty, barriers, and caregiver burden among help-seekers from an early detection service for dementia. Methods: The study included 105 dyads of caregivers and people with suspected dementia from a dementia early detection service in Hong Kong. Caregivers rated their perceived difficulty in help-seeking and perceived barriers. Caregiver burden was assessed using the 12-item version of Zarit Burden Interview. Cognitive performance, daily activities functioning, neuropsychiatric symptoms, and quality of life of the person with suspected dementia were assessed. Results: Majority (47/105; 45%) of help-seekers found help-seeking easy or very easy; 39% found the experience neutral; and 16.2% found it difficult or very difficult. Caregiver burden differed among caregivers with different perceived difficulty level (F=13.7; p<0.01). Perceived help-seeking difficulty was related to perceived barriers of "lack of awareness of symptoms", "inaccessible service", and "lack of time". Regression analysis showed that perceived difficulty in help-seeking, quality of life of the person with suspected dementia, and neuropsychiatric symptoms explained a significant proportion of the variance in caregiver burden (R2=0.49, F(3, 97)=33.06, p<0.01). Cognitive and daily activities functioning were insignificant when included in the model. Conclusion: Ease of help-seeking predicts caregiver burden upon entering dementia service among other known predictors of burden, including cognitive and functioning impairment levels. Addressing help-seeking barriers at system level may contribute to reduced caregiver burden.